Universal character, phase model and topological strings on [Formula omitted] - Wang, Na; Li, Chuanzhong (The European physical journal. C, Particles and fields, 2019)
In this paper, we consider two different subjects: the algebra of universal characters [Formula omitted] (a generalization of Schur functions) and the phase model of strongly correlated bosons. We find that the two-site generalized phase model can be realized in the algebra of universal characters, and the entries in the monodromy matrix of the phase model can be represented by the vertex operators [Formula omitted] which generate universal characters. Meanwhile, we find that these vertex operators can also be used to obtain the A-model topological string partition function on [Formula omitted].